2021
DOI: 10.1021/acs.energyfuels.0c03376
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Z-Scheme Heterojunction Polyhedral-Shaped BiOIO3/MIL-53(Fe) Photocatalyst for Enhancing Gaseous Hg0 Removal

Abstract: A Z-scheme heterojunction polyhedral-shaped BiOIO 3 /MIL-53(Fe) photocatalyst is prepared by a solvothermal method. The samples are characterized by XRD, XPS, SEM, TEM, FT-IR, UV−vis, PL, and other material characterization analysis methods. The photocatalytic performance of photocatalysts is studied for removal of vapor-phase mercury (Hg 0 ) under visiblelight irradiation. The results suggest that the Hg 0 removal efficiency of the BiOIO 3 /MIL-53(Fe) composite is significantly improved compared with that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…In this sense it has greatly attracted researchers because of its exceptional tunability and functionality. [52][53][54][55][56][57] Moreover, researchers have also aimed at designing effective functionalized MOF catalysts with organic and organometallic moieties. 48,[57][58][59][60][61][62] These methods which were applied to modify various types of catalysts, 61 heteropoly acids and other transition metal-catalysts have been successfully encapsulated into the pores of MIL-53 (Fe).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense it has greatly attracted researchers because of its exceptional tunability and functionality. [52][53][54][55][56][57] Moreover, researchers have also aimed at designing effective functionalized MOF catalysts with organic and organometallic moieties. 48,[57][58][59][60][61][62] These methods which were applied to modify various types of catalysts, 61 heteropoly acids and other transition metal-catalysts have been successfully encapsulated into the pores of MIL-53 (Fe).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the scavenger tests of the Bi-11.0 sample were conducted to explore the reactive oxygen species (ROS) in the photocatalytic process for 30 min. The benzoquinone (BQ) and isopropanol (IPA) capture agents were used to selectively capture superoxide radicals (·O 2 – ) and hydroxyl radicals (·OH), respectively. , As shown in Figure a, when the capture agents were added to the catalytic reaction system, the mercury-removal efficiency of Bi-11.0 decreased significantly. This phenomenon indicated that the ·O 2 – and ·OH reactive species played a significant role in the photocatalytic reaction process for Hg 0 removal.…”
Section: Resultsmentioning
confidence: 99%
“…36 Highly porous metal oxide aerogels are also beneficial for decomposing gas-phase pollutants and toxic chemicals in the air. 238 An Ag/TiO 2 composite aerogel was prepared for removing toluene in the flowing air. 239 The results showed that 95.7% of 300 ppm of toluene was decomposed under light irradiation.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…Highly porous metal oxide aerogels are also beneficial for decomposing gas-phase pollutants and toxic chemicals in the air . An Ag/TiO 2 composite aerogel was prepared for removing toluene in the flowing air .…”
Section: Photocatalytic Applications Of Metal Oxide Aerogelsmentioning
confidence: 99%